Costs and cost-effectiveness of three point-of-use water treatment technologies added to community-based treatment of severe acute malnutrition in Sindh Province, Pakistan - Eleanor Rogers; Hannah Tappis; Shannon Doocy; Karen Martínez; Nicolas Villeminot; Ann Suk; Deepak Kumar; Silke Pietzsch; Chloe Puett (Taylor & Francis Group, 2019)
Background: Severe acute malnutrition (SAM) is a major global public health concern. Despite the cost-effectiveness of treatment, ministries of health are often unable to commit the required funds which limits service coverage. Objective: A randomised controlled trial was conducted in Sindh Province, Pakistan, to assess whether adding a point of use water treatment to the treatment of SAM without complications improved its cost-effectiveness. Three treatment strategies - chlorine disinfection (Aquatabs); flocculent disinfection (Procter and Gamble Purifier of Water [P&G PoW]) and Ceramic Filters - were compared to a standard SAM treatment protocol. Methods: An institutional perspective was adopted for costing, considering the direct and indirect costs incurred by the provider. Combining the cost of SAM treatment and water treatment, an average cost per child was calculated for the combined interventions for each arm. The costs of water treatment alone and the incremental cost-effectiveness of each water treatment intervention were also assessed. Results: The incremental cost-effectiveness ratio for Aquatabs was 24 US dollars (USD), making it the most cost-effective strategy. The P&G PoW arm was the next least expensive strategy, costing an additional 149 USD per additional child recovered, though it was also the least effective of the three intervention strategies. The Ceramic Filters intervention was the most costly strategy and achieved a recovery rate lower than the Aquatabs arm and marginally higher than the P&G PoW arm. Conclusions: This study found that the addition of a chlorine or flocculent disinfection point-of-use drinking water treatment intervention to the treatment of SAM without complications reduced the cost per child recovered compared to standard SAM treatment. To inform the feasibility of future implementation, further research is required to understand the costs of government implementation and the associated costs to the community and beneficiary household of receiving such an intervention in comparison with the existing SAM treatment protocol. Trial registration: ClinicalTrials.gov identifier: NCT02751476.